Structure and distribution of a threatened muddy biotope in the south-eastern North Sea. (1st February 2020) - Gutow, Lars; Günther, Carmen-Pia; Ebbe, Brigitte; Schückel, Sabine; Schuchardt, Bastian; Dannheim, Jennifer; Darr, Alexander; Pesch, Roland
Abstract: Understanding the distribution and structure of biotopes is essential for marine conservation according to international legislation, such as the European Marine Strategy Framework Directive (MSFD). The biotope 'Sea Pen and Burrowing Megafuna Communities' is included in the OSPAR list of threatened and/or declining habitats. Accordingly, the MSFD prescribes a monitoring of this biotope by the member states of the EU. In the German North Sea, however, the distribution and spatial extent of this biotope as well as the structuring of its benthic species inventory is unknown. We used an extensive geo-referenced dataset on occurrence, abundance and biomass of the benthic infauna of the south-eastern North Sea to estimate the distribution of the biotope and to characterize the associated infauna assemblages. Sediment preferences of the burrowing megafauna, comprising decapod crustaceans and echiurids, were identified and the core distribution areas of the burrowing megafauna were modelled using Random Forests. Clusters of benthic infauna inside the core distribution areas were identified by fuzzy clustering. The burrowing megafauna occurred on a wide range of sediments with varying mud contents. The core distribution area of the burrowing megafauna was characterized by elevated mud content and a water depth of 25–55 m. The analysis of the benthic communities and their relation to sedimentological conditions identified four infauna clusters of slightly varying species composition. The biotope type 'Sea Pen and Burrowing Megafuna Communities' is primarily located inside the paleo valley of the river Elbe and covers an area of 4980 km 2 . Dedicated monitoring will have to take into account the spatial extent and the structural variability of the biotope. Our results can provide a baseline for the evaluation of the future development of the environmental status of the biotope. The maps generated herein will facilitate the communication of information relevant for environmental management to authorities and policy makers. Highlights: The distribution of an endangered benthic biotope in the SE North Sea is modelled. Benthic communities of the muddy biotope are identified. Analyses are based on an extensive, multi-annual dataset. Results facilitate planning of mandatory environmental monitoring. Maps are provided for communication of results to stakeholders.